Antibody-Based Strategies to Prevent and Treat Influenza - Shriver, Zachary; Trevejo, Jose M.; Sasisekharan, Ram (Frontiers in Immunology, 2015)
Passive immunization using antibodies has been suggested to offer several benefits in comparison to other antiviral treatment options. The potential for seasonal protection arising from a single injection of antibodies is appealing and has been pursued for a number of infectious agents. However, until recently, antibody-based strategies to combat infectious agents has been hampered due to the fact that typical antibodies have been found to be strain-specific, with the virus evolving resistance in many cases. The discovery of broadly neutralizing antibodies (bNAbs) in, for example, influenza, dengue virus, and HIV, which bind to multiple, structurally-diverse strains has provided renewed interest in this area. This review will focus on new technologies that enable the discovery of bNAbs, the challenges and opportunities of immunotherapies as an important addition to existing antiviral therapy, and the role of antibody discovery in informing rational vaccine discovery – with agents targeting influenza specifically addressed. Multiple agents have entered the clinic and raise the possibility that a single antibody or small combination of antibodies can effectively neutralize a wide variety of strains. However, challenges remain - including combating escape variants, pharmacodynamics of antibody distribution, and development of efficacy biomarkers beyond virologic endpoints.